Love and peace across generations: biobehavioral systems and global partnerships - Leckman, JF; Pavarini, G; Ponguta, LA; Staiti, H; Hein, SD; Hanöz-Penney, S; Rubinstein, J; Pruett, KD; Yazgan, MY; McCarthy, MF; Fallon, NS; Hartl, FJ; et al. (Elsevier, 2021)
Children's environments - especially relationships with caregivers - sculpt not only developing brains but also multiple bio-behavioral systems that influence long-term cognitive and socioemotional outcomes, including the ability to empathize with others and interact in prosocial and peaceful ways. This speaks to the importance of investing resources in effective and timely programs that work to enhance early childhood development (ECD) and, by extension, reach communities at-scale. Given the limited resources currently devoted to ECD services, and the devastating impact of COVID-19 on children and communities, there is a clear need to spur government leaders and policymakers to further invest in ECD and related issues including gender and racial equity. This essay offers concrete examples of scholarly paradigms and leadership efforts that focus on child development to build a peaceful, equitable, just, and sustainable world. As scholars and practitioners, we need to continue to design, implement, assess, and revise high-quality child development programs that generate much-needed evidence for policy and programmatic changes. We must also invest in global partnerships to foster the next generation of scholars, practitioners, and advocates dedicated to advance our understanding of the bio-behavioral systems that underlie love, sociality, and peace across generations. Especially where supported by structural interventions, ECD programs can help create more peaceful, just, and socially equitable societies.